Genetic variability, character association and path coefficient analysis in China aster (Callistephus chinensis) - BHARGAV, VELURU; KUMAR, RAJIV; RAO, T MANJUNATHA; BHARATHI, T USHA (The Indian Journal of Agricultural Sciences, 2019)
Forty-two genotypes of China aster [Callistephus chinensis (L.) Nees] were evaluated in RBD with two replications for growth, flowering, yield and postharvest traits to determine the variability, heritability, genotypic and phenotypic coefficient of variation, correlation and path coefficient among 13 quantitative traits, based on which selection may be made. The study was carried out at the Division of Floriculture and Medicinal Crops, ICAR-Indian Institute of Horticultural Research, Hesaraghatta, Bengaluru during 2015–16 and 2016–17. Results revealed that magnitude of the phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV) for all the traits. High (>20%) PCV and GCV was recorded for plant height, number of leaves per plant, plant spread, flower stalk length, 100 flower weight, number of flowers per plant and weight of flowers per plant. Heritability estimates ranged from 92.32% (number of leaves per plant) to 99.84% (100 flower weight). High heritability coupled with high genetic gain as per cent of mean was recorded for all the traits studied. The weight of flowers per plant was significant and positively correlated with all the economic traits, except for shelf life. Path coefficient analysis using correlation coefficients revealed that number of flowers per plant contributed highest positive direct effect on weight of flowers per plant, followed by weight of 100 flowers. Therefore, the selection on the basis of traits, viz. plant height, number of leaves per plant, plant spread, flower stalk length, 100 flower weight, number and weight of flowers per plant will be more effective for improvement of traits in breeding of China aster.